Association between muscle strength gains and biventricular cardiac remodeling in response to high-intensity resistance training in healthy untrained males: a longitudinal study - Nicolas Pamart; Joffrey Drigny; Hélène Azambourg; Marion Remilly; Kamal Lahjaily; Amélia Rocamora; Francois Tournoux; Eric Saloux; Emmanuel Reboursière; Antoine Gauthier; Amir Hodzic (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background High-intensity resistance training induces structural and functional adaptations in skeletal muscle, yet its impact on cardiac remodeling remains debated. This study aimed to investigate the longitudinal biventricular cardiac response to a 20-week high-intensity resistance training program in previously untrained, healthy males and examine the association between muscle strength gains and cardiac remodeling. Methods Twenty-seven male volunteers (aged 18–40 years) participated in a high-intensity resistance training program for 20 weeks. Assessments at baseline, 12 weeks, and 20 weeks included resting blood pressure, electrocardiogram (ECG), three-dimensional transthoracic echocardiography (3DTTE), cardiopulmonary exercise testing ( $$\:\dot{V}$$ O2peak), isokinetic dynamometry for muscle strength, and actimetry recordings. Time effects were analyzed using one-way repeated measures ANOVA (P < 0.05). Results Twenty-two participants completed the study. Resistance training led to significant reductions in arterial systolic and diastolic blood pressure and heart rate. After 20 weeks of training, 3DTTE showed a significant increase in left ventricular (LV) mass (120.1 ± 15.4 g vs. 133.7 ± 16.3 g, p < 0.001), without inducing LV hypertrophy. Balanced increases were observed in LV end-diastolic volume (146.4 ± 18.9 ml vs. 157.9 ± 19.6 ml, p < 0.001) and right ventricular (RV) end-diastolic volume (119 ± 19.4 ml vs. 129.2 ± 21.6 ml, p < 0.001). LV and RV systolic and diastolic function remained unchanged. There were no changes in $$\:\dot{V}$$ O2peak or daily activity levels. Maximal muscle strength in the quadriceps, hamstrings, triceps, and biceps was significantly correlated with LV and RV end-diastolic volumes and LV mass (p ≤ 0.001). Conclusion The resistance training program resulted in significant and rapid muscle strength gains and reduced blood pressure. Cardiac adaptations, including moderate biventricular dilatation, were observed without changes in cardiac function or $$\:\dot{V}$$ O2peak and were associated with muscle strength gains. Our study highlights that intensive resistance training in novice male resistance trainers induces an adaptive cardiac response, reflecting a physiological adaptation linked to enhanced muscle performance. Trial registration ClinicalTrials.gov ID: NCT04187170.